Responsibility of states for damages to foreigners in a tentative period. The Spanish chapter of the Cerruti case and other claims of Italian subjects against Colombia (1886-1904) - Domínguez Benito, Héctor (Cuadernos de Historia del Derecho, 2025)
By means of the Matéus-Menabrea Protocol of 1886, Colombia and Italy agreed to submit to the Government of Spain the decision as to whether Ernesto Cerruti and other Italian subjects living in Colombia should be compensated for the damages they had suffered as a result of administrative responsibility. Historians have so far not paid much attention to the Spanish sources relevant to this agreement, and have focused only on examining the first phase of this case: the millionaire lawsuit concerning Cerruti. This paper aims to provide a panoramic view of the two phases of the litigation in Spain, highlighting the peculiar status granted to the mediator –or, rather, arbitrator– and contextualizing the complex trajectory of the case within a broader scenario of profound transformations, during which international law was still in an experimental stage.